Knowledge Goes Pop From Conspiracy Theory to Gossip - Birchall, Clare (Culture Machine, 2006)
A voice on late night radio tells you that a fast food joint injects its food with drugs that make men impotent. A colleague asks if you think the FBI was in on 9/11. An alien abductee on the Internet claims extra-terrestrials have planted a microchip in her left buttock. 'Julia Roberts in Porn Scandal' shouts the front page of a gossip mag. A spiritual healer claims he can cure chronic fatigue syndrome with the energizing power of crystals . . . What do you believe? Knowledge Goes Pop examines the popular knowledges that saturate our everyday experience. We make this information and then it shapes the way we see the world. How valid is it when compared to official knowledge and why does such (mis)information cause so much institutional anxiety? Knowledge Goes Pop examines the range of knowledge, from conspiracy theory to plain gossip, and its role and impact in our culture.What do you believe? This title examines the popular knowledges that saturate our everyday experience. How valid is it when compared to official knowledge and why does such (mis)information cause so much institutional anxiety? It examines the range of knowledge, from conspiracy theory to plain gossip, and its role and impact in our culture.Clare Birchall is Senior Lecturer at Middlesex University.